Advancing Intelligent Manufacturing in the Automotive Industry for Enhanced Innovation and Sustainability of New Energy Vehicles - Liu Zheyu (MATEC Web of Conferences)
Intelligent manufacturing technology is revolutionizing the production processes in the automotive industry through enhanced efficiency, flexibility, and intelligence. This review examines the current applications and future trends of intelligent manufacturing in the automotive sector, aiming to inform technological innovation and strategic planning. The paper begins by outlining the development and significance of intelligent manufacturing in the context of the automotive industry. Key technologies such as the industrial Internet, mechatronics, industrial robots, and digital factories are then highlighted, with an analysis of their roles in improving manufacturing efficiency and product quality. Through a comprehensive literature review and case analysis, the integrated application of these technologies is explored, particularly their innovations in production line design and impact on new energy vehicles. The paper concludes by summarizing how intelligent manufacturing technology is driving the automotive industry’s transformation towards greener and smarter production, and it proposes future research directions and addresses technical challenges.